Citizen participation and social control: challenges for veedurias (2016)
Veedurías currently has a too big challenge, as is the empowerment of citizens to their rights and duties, it is through citizen participation and social control that citizens can develop our ideas to build a better city and can ensure that leaders who chose through citizen participation mechanisms such as voting, representing each of these ideas and goals that unite us under one territory, culture, resources, among others.